2019
DOI: 10.5455/javar.2019.f315
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological study on the tongue of the duck in the Caribbean with relation to feeding habit and #8195;

Abstract: Objective: The objective of this study was to give detailed descriptions of the morphological and histological structures of the tongue of the Muscovy duck as it relates to their feeding habit. Materials and Methods: Ten adult Muscovy ducks weighing 2–4 kg were used. The ducks were slaughtered and their oral cavities were opened to detect in situ position of the tongues. Each tongue was dissected and examined grossly. Samples of various parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
6
2
0
Order By: Relevance
“…The tongue of the Khaki Campbell duck occupied the floor of the oropharyngeal cavity except for the free tip of the bottom of the bill, rostrally. It was similar to the findings of in Muscovy duck, Abdalla et al (2011) in the duck, Mohamed (2004) in quails, Abd El-Fatah et al (2000) in turkey, Koch (1973) in fish eaters birds, Mohamed (2019) in Caribbean duck and Skieresz-Szewczyk & Jackowiak (2016) in domestic duck. The tongue fills the oral cavity in ducks and geese, as Nickel et al (1977) reported.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The tongue of the Khaki Campbell duck occupied the floor of the oropharyngeal cavity except for the free tip of the bottom of the bill, rostrally. It was similar to the findings of in Muscovy duck, Abdalla et al (2011) in the duck, Mohamed (2004) in quails, Abd El-Fatah et al (2000) in turkey, Koch (1973) in fish eaters birds, Mohamed (2019) in Caribbean duck and Skieresz-Szewczyk & Jackowiak (2016) in domestic duck. The tongue fills the oral cavity in ducks and geese, as Nickel et al (1977) reported.…”
Section: Discussionsupporting
confidence: 88%
“…The present study under discussion revealed that the shape of the tongue of the Khaki Campbell duck was narrow and elongated, as reported by in Muscovy duck, Abdalla et al (2011) in the duck, Mohamed R. (2019) in Caribbean duck, Skieresz-Szewczyk and Jackowiak (2016) in domestic duck whereas triangular-shaped tongue was reported by Bansal et al, 2017 in chicken, by Calabro et al (2009) in Podiceps nigricollis, Sula Variegata and Ardeola grayii, elongated triangularshaped tongue in rock-pigeon was reported by Al-Jumaily et al ( 2013), Iwasaki et al (1997) reported semicircular tongue in male ostrich. The tongue of the Khaki Campbell duck consisted of the root, body with lingual prominence, and apex; similar findings were observed by El Bakary et al (2016) in Anas crecca, by Sridevi et al (2018) in mute swan, Mohamed (2019) in Caribbean duck, Skieresz-Szewczyk and Jackowiak (2016) in domestic duck. Root, body, apex, raised area, and a line-like extension was found in the tongue in pati duck by Sarma and Anil (2015).…”
Section: Discussionsupporting
confidence: 87%
“…The current SEM study demonstrated three recognized parts in the tongue of the two birds as the anterior part (apex), the middle part (corpus) and the posterior part (radix). Similar findings were observed in duck (Mohamed, 2019). The total length of Lonchura oryzivora's tongue was about 8.5 mm.…”
Section: Ultrastructural Findingssupporting
confidence: 87%
“…The histological results showed that all salivary glands lying in the pharynx of both species were observed in the lamina propria. Several published articles were boosted these results (salivary glands in pharynx located within lamina propria) as lingual glands in duck (Mohamed, 2019), spheniopterygoid glands in turkey (Sayed et al, 2016) and duck (Madkour et al, 2020), as well as, Hodges (1974) stated that the glands in pharynx at base of lamina propria or within submucosa. Whilst large number of data are demonstrated salivary glands within submucosa in different avian species as caudal lingual glands in laughing dove (Abumandour and El-Bakary, 2019), quail (Uppal et al, 2014), kestrel and owl (Abumandour and El-Bakary, 2017b), penguin (Kobayashi et al, 1998) and circoartynoid salivary glands in duck (Mohamed et al, 2018).…”
Section: Discussionmentioning
confidence: 96%